State, Society and the Market in Contemporary Vietnam: Property, Power and Values, 1st edition - Tai, Hue-Tam Ho (Routledge, 2020)
Lively debates around property, access to resources, legal rights, and the protection of livelihoods have unfolded in Vietnam since the economic reforms of 1986. Known as Doi Moi (changing to the new), these have gradually transformed the country from a socialist state to a society in which a communist party presides over a neoliberal economy.